The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1007/s11434-008-0149-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of porous microstructures on NiTi alloy surface with femtosecond laser pulses

Abstract: Porous microstructures on Nickel-Titanium (NiTi) alloy surfaces were prepared by linearly polarized femtosecond lasers with moving focal point at a certain speed. It was found that various novel microstructures from feather-like ripples to cluster-like porous textures could be formed with increasing laser energy. Particularly, when the laser energy was 400 μJ, a periodic porous metal surface was generated. Measurement of X-ray diffraction showed that the grains on the sample surface were refined through femtos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…By using a femtosecond laser, the well-ordered porous microstructures from featherlike ripples to cluster-like porous textures can be formed on metal stent surface. [156] Accordingly, SMCs-biomimetic microstructure in the nano-micro range can be produced on implant surfaces to promote the SMCs adhesion. 316L SS stents with SMCs-biomimetic micro-nanopatterns were obtained according to the morphology of SMCs recorded by atomic force microscopy (Figure 2F).…”
Section: Surface Patternsmentioning
confidence: 99%
“…By using a femtosecond laser, the well-ordered porous microstructures from featherlike ripples to cluster-like porous textures can be formed on metal stent surface. [156] Accordingly, SMCs-biomimetic microstructure in the nano-micro range can be produced on implant surfaces to promote the SMCs adhesion. 316L SS stents with SMCs-biomimetic micro-nanopatterns were obtained according to the morphology of SMCs recorded by atomic force microscopy (Figure 2F).…”
Section: Surface Patternsmentioning
confidence: 99%
“…就显色机理而言生物体表面呈 现的五颜六彩的颜色分为化学色以及物理色 [80] , 化学 色是指生物体内的色素对光进行吸收致使表面呈现不 同的色彩, 而物理色则是来源于表面的微结构产生的 薄膜干涉、光子晶体、光栅衍射以及散射产生的效果, 即为结构色 [81] . Vorobyev [79,82~85] 优势 [94] , 可以在多种表面上制造有序的周期性微纳 米结构 [95,96] . ; the enlarged region between endothelium and vascular smooth muscle in circumstance of (e) primitive blood vessels, (f) NTS-implanted blood vessels and (g) LTS-implanted blood vessels; tissue adhesion to the (h) normal electrode substrate (i) biomimetic electrode and (j) coupled biomimetic electrode; the SEM images of the surface of (k) normal electrode substrate and (l) coupled biomimetic electrode substrate [92,93] 评 述 Han等人 [93] In natural selection, "survival of the fittest" is the prevailing mechanism where organisms have constantly been evolving to adapt themselves to their surroundings.…”
Section: 超疏水性表面mentioning
confidence: 99%
“…A research [53] on porous nitinol interbody fusion device revealed that nitinol has perfect biocompatibility on the dura mater, spinal cord and nerve roots, lymph nodes (abdominal para-aortic), and organs (kidneys, spleen, pancreas, liver, and lungs). Liang et al [54] prepared porous microstructures on Nickel-Titanium (NiTi) alloy surfaces by linearly polarized femtosecond lasers with moving focal point at a certain speed. This investigation provides a new approach to improve the biocompatibility of NiTi-based implant devices.…”
Section: Corrosion Properties and Biocompatibility Of Niti-smamentioning
confidence: 99%